Association between blood pressure variability and clinical outcomes after successful recanalization in patients with large vessel occlusion stroke after mechanical thrombectomy - Lu, You; Shen, Rui; Lin, Wenjian; Zhou, Xiaoyu; Hu, Jian; Zhang, Quanbin (Frontiers in Neurology, 2022)
Objective Nearly half of patients who undergo mechanical thrombectomy (MT) do not experience a favorable outcome. The association between blood pressure fluctuation and clinical outcomes after successful MT is controversial. We evaluated the influence of blood pressure variability (BPV) on the clinical outcomes of stroke patients with large vessel occlusion (LVO) who underwent successful recanalization after MT. Methods Patients with anterior circulation LVO stroke who underwent successful emergency MT (modified Thrombolysis in Cerebral Infarction, mTICI ≥ 2b) at the Shanghai Tenth People's Hospital of Tongji University from 2017 to 2021 were enrolled. Multivariate logistic models were used to investigate the association between BPV (mean arterial pressure [MAP] assessed using the standard deviation [SD]) and clinical outcomes. The primary outcome was 90-day modified Rankin Scale scores (mRS), and the secondary outcomes were 30-day mortality and symptomatic intracranial hemorrhage (sICH). Results A total of 458 patients (56.8% men), with a mean age of 72 ± 1 years, were enrolled. Among them, 207 (45.2%) patients had unfavorable functional outcomes (mRS score 3–6) at 90 days, 61 (13.3%) patients died within 30 days, and 20 (4.4%) patients had sICH. In a fully adjusted model, BPV was associated with a higher risk of a 90-day mRS score of 3–6 (P = 0.04), 30-day mortality (P < 0.01), and sICH (P < 0.01). A significant interaction between MAP SD and rescue futile recanalization treatment was observed (P < 0.01). Conclusions Among patients with LVO stroke who underwent successful recanalization, higher BPV was associated with worse functional outcomes, especially in those who underwent rescue treatment.